Analysis of playing styles in the 2023 FIFA Women's World Cup - López-Araya, S.; Lago-Peñas, C.; Pino-Ortega, J.; Ibáñez, S. J. (International Journal of Sports Science and Coaching, 2026)
Despite the growing interest in Women's Football, there is still limited evidence on the factors that determine success in this sport. The aim of this study was to analyze the Playing Styles of the national teams that participated in the 2023 FIFA Women's World Cup. The sample included all matches played in the tournament (n = 64). A total of 33 Performance Indicators were analyzed, obtained from the official FIFA website. Principal Component Analysis was used to reduce the number of variables, and upper and lower quartiles were calculated both overall and by confederation. The main results suggest that three Playing Styles were used during the 2023 FIFA Women's World Cup: Counterattack-Finishing, Elaborated Attack, and Reactive-Defensive. The use of Playing Styles varied across teams, showing that sporting success was based on maintaining a balance between Counterattack-Finishing and Elaborated Attack. Teams within the same confederation also differed in the Playing Styles they used, indicating the application of different strategies rather than a single shared trend. These findings may help optimize performance in Women's Football by supporting the adjustment of strategies to the most frequently used Playing Styles and by informing planning for future competitions.